2007
DOI: 10.4161/cc.6.2.3718
|View full text |Cite
|
Sign up to set email alerts
|

The KLF Family of Transcriptional Regulators in Cardiomyocyte Proliferation and Differentiation

Abstract: Unlike other organs, the adult heart has limited regenerative potential owing to the inability of postnatal cardiomyocytes to undergo proliferative growth. As a result, ischemic heart disease continues to be a major cause of morbidity and mortality worldwide. Elucidating the molecular pathways of cardiomyocyte differentiation and proliferation holds great promise for human health. In a recent paper we employed a multidisciplinary approach to identify a novel pathway required for cardiomyocyte growth and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 37 publications
3
56
0
Order By: Relevance
“…In pulmonary smooth muscle cells, GATA4 appears to be important for cell proliferation, and overexpression of a repressor form of GATA4 suppresses cyclin D2 expression (73), which supports the direct activation of Cyclin D2 by GATA4 observed in our studies. Similarly, GATA1 induces the sustained expression of cyclin D1 in a myeloid cell line (77), and GATA4 cooperates with the Kruppel-like factor KLF13 to activate Cyclin D1 in Xenopus laevis (46). All of these studies, taken together with the work presented here, support a model in which GATA factors may function generally as regulators of the cell cycle in multiple tissues.…”
Section: Discussionsupporting
confidence: 67%
“…In pulmonary smooth muscle cells, GATA4 appears to be important for cell proliferation, and overexpression of a repressor form of GATA4 suppresses cyclin D2 expression (73), which supports the direct activation of Cyclin D2 by GATA4 observed in our studies. Similarly, GATA1 induces the sustained expression of cyclin D1 in a myeloid cell line (77), and GATA4 cooperates with the Kruppel-like factor KLF13 to activate Cyclin D1 in Xenopus laevis (46). All of these studies, taken together with the work presented here, support a model in which GATA factors may function generally as regulators of the cell cycle in multiple tissues.…”
Section: Discussionsupporting
confidence: 67%
“…KLF13 (Krüppel-like factor 13) is a zinc finger transcription factor known to play a role in proliferation, differentiation, cell cycle progression, and apoptosis [Chen et al, 2001;Kaczynski et al, 2003;Nemer and Key Words FGFR3 ؒ KLF13 ؒ miRNA ؒ Oral cancer Abstract KLF13 and FGFR3 have important cellular functions and each is believed to play a role in cancer. KLF13 is a transcription factor required for the expression of several oncogenes.…”
mentioning
confidence: 99%
“…Recently, it has been reported that KLF family transcriptional factors regulates versatile type of differentiation [22].…”
Section: Discussionmentioning
confidence: 99%